HAPLN1 Affects Cell Viability and Promotes the Pro-Inflammatory Phenotype of Fibroblast-Like Synoviocytes - Chen, Yong; Wang, Baojiang; Chen, Yanjuan; Wu, Qunyan; Lai, Wing-Fu; Wei, Laiyou; Nandakumar, Kutty Selva; Liu, Dongzhou (Frontiers in Immunology, 2022)
HAPLN1 maintains aggregation and the binding activity of extracellular matrix (ECM) molecules (such as hyaluronic acid and proteoglycan) to stabilize the macromolecular structure of the ECM. An increase in HAPLN1 expression is observed in a few types of musculoskeletal diseases including rheumatoid arthritis (RA); however, its functions are obscure. This study examined the role of HAPLN1 in determining the viability, proliferation, mobility and pro-inflammatory phenotype of RA- fibroblast-like synoviocytes (RA-FLSs) by using small interfering RNA (siHAPLN1), over-expression vector (HAPLN1OE) and a recombinant HAPLN1 (rHAPLN1) protein. HAPLN1 was found to promote proliferation but inhibit RA-FLS migration. Metformin, an AMPK activator, was previously found by us to be able to inhibit FLS activation but promote HAPLN1 secretion. In this study, we confirmed the up-regulation of HAPLN1 in RA patients, and found the positive relationship between HAPLN1 expression and the AMPK level. Treatment with either si-HAPLN1 or HAPLN1OE down-regulated the expression of AMPK-ɑ gene, although up-regulation of the level of p-AMPK-ɑ were observed in RA-FLSs. si-HAPLN1 down-regulated the expression of proinflammatory factors like TNF-ɑ, MMPs and IL-6; while HAPLN1OE up-regulated their levels. qPCR assay indicated that the levels of TGF-β, ACAN, Fibronectin, collagen Ⅱ, and Ki-67 were down-regulated upon si-HAPLN1 treatment; while HAPLN1OE treatment led to up-regulation of ACAN, Ki-67 and down-regulation of cyclin-D1. Proteomics of si-HAPLN1, rHAPLN1 and mRNA-Seq analysis of rHAPLN1 confirmed the functions of HAPLN1 in the activation of inflammation, proliferation, cell adhesion, and strengthening of ECM functions. Our results for the first time demonstrate the function of HAPLN1 in promoting the proliferation and pro-inflammatory phenotype of RA-FLSs, thereby contributing to RA pathogenesis. Future in-depth studies are required for better understanding the role of HAPLN1 in RA.